ESSENTIAL TRACE METALS IN HEALTH AND DISEASE - Makević, Vedrana; Ilić, Anđelija; de Luka, Silvijo (Medicinski podmladak, 2023)
Essential trace metals (Fe, Zn, Cu, Mn, Mo, Co) are involved in high number of physiological and metabolic activities and therefore have substantial role in organism. Thus, their balance is tightly regulated on levels of absorption, transport, and storage in the organism. They can alter human health in both deficiency and overload conditions. On one hand in deficiency health problems are due to reduction of their physiological activities. On the other hand, Fe, Cu and Co are redox active metals and their increase can cause severe tissue damage through oxidative stress. Many well-established diseases like iron and copper deficiency anemia, hemochromatosis, Menkes and Wilson disease, acrodermatitis enteropathica are consequence of essential metal alterations. Nowadays, trace metals alterations are also found to be implicated in neurodegenerative disease, cancers, atherosclerosis, and diabetes. Those diseases represent enormous health problems in contemporary society and trace metals might help to further elucidate their pathogenesis and potentially even treatment. In the present study, we review essential trace metals kinetic and physiology, as well as their roles in disease pathophysiology.